D22 Compensation in preclinical huntington's disease: evidence from the track-on HD study. (13th September 2016) - Gregory, Sarah; Klöppel, Stefan; Scheller, Elisa; Minkova, Lora; Razi, Adeel; Durr, Alexandra; Roos, Raymund AC; Leavitt, Blair R; Papoutsi, Marina; Bernhard Landwehrmeyer, G; Reilmann, Ralf; Borowsky, Beth; et al.
Abstract : Background: Cognitive and motor task performance in premanifest Huntington's disease (HD) gene-carriers is often within normal ranges prior to clinical diagnosis, despite loss of brain volume in regions involved in these tasks. This indicates ongoing compensation, with the brain maintaining function in the presence of neuronal loss. However, thus far, compensatory processes in HD have not been explicitly addressed in statistical models. Aims: Using a new statistical model, which incorporates individual variability related to structural burden (i.e., loss of brain volume) and behaviour, we sought to identify functional correlates of compensation in premanifest-HD gene-carriers. Methods: We investigated the modulatory effects of regional brain atrophy, indexed by structural measures of disease load, on the relationship between performance and brain activity (or connectivity) using task-based and resting-state functional MRI. Results: Consistent with compensation, higher atrophy was associated with increased performance-related activity of the right parietal cortex during a working memory task. Similarly, higher functional coupling between the right dorsolateral prefrontal cortex and a left hemisphere network in the resting-state predicted better cognitive performance in individuals with higher disease burden. Such patterns were not detectable for the left hemisphere or for motor tasks. Conclusion: Our findings provide evidence for active compensatory processes in premanifest-HD for cognitive demands and suggest a higher vulnerability of the left hemisphere to the effects of regional atrophy.